QUick Count Analisis Akurasi dan Efisiensi pada Quick Count Menggunakan Ambang MinMax - Riadi Marta Dinata (JURNAL REKAYASA INFORMASI, 2023)
Quick Count is a method of quickly calculating general election results using data from a sample of polling stations (TPS), which are selected randomly and proportionally. In this research, researchers propose the Minmax Quick Count approach to Simple Random Sampling (SRS) to find the optimal sampling technique. Namely to find a comparison of accuracy and efficiency between Primary-SRS against SRS using Minimum and Maximum voter vote thresholds. The quick count case study is the DKI DKI Jakarta area, using validated test data "Vote Count Results for the 2019 Indonesian Presidential & Vice Presidential Election".The peak of effectiveness and efficiency in the case of Quick Count data is at a Confidence Level of 90%, Margin of Error of 0.01%, with the number of TPS selected being 0.16% of the population (deviasi 2.24%). And the maxSRS method provides average results that are closer to the actual average value of 3% compared to the primer SRS and minSRS methods.